2013
DOI: 10.1111/ajo.12075
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor muscle training improves quality of life of women with urinary incontinence: a prospective study

Abstract: Pelvic floor muscle training appears to be an effective first-line intervention for improving urinary symptoms and QoL of women presenting with urinary incontinence. Future studies on long-term effectiveness and cost-effectiveness are also required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 24 publications
2
25
0
1
Order By: Relevance
“…Women with USI who did not improve after pelvic floor exercise were offered TO-TVT. 5 Women who had USI only underwent TO-TVT surgery, while women with both USI and POP received TO-TVT and concomitant PFR surgery. Vaginal hysterectomy and anterior or posterior colporrhaphy were performed accordingly as PFR surgery.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Women with USI who did not improve after pelvic floor exercise were offered TO-TVT. 5 Women who had USI only underwent TO-TVT surgery, while women with both USI and POP received TO-TVT and concomitant PFR surgery. Vaginal hysterectomy and anterior or posterior colporrhaphy were performed accordingly as PFR surgery.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4] It has a significant adverse impact on quality of life for 12% of women with the condition in Hong Kong. [3][4][5] Surgical treatment with tension-free vaginal tape New knowledge added by this study • Transobturator tension-free vaginal tape (TO-TVT) is an effective treatment for urinary stress incontinence in women who received it alone or with concomitant pelvic floor repair surgery for pelvic organ prolapse (POP).…”
Section: Introductionmentioning
confidence: 99%
“…Fan et al evaluated the effects of PFMT on the urinary symptoms and quality of life. Participants participating in 3 to 9 months of PFMT observed improvement both in their urinary symptom scores and in their quality of life regardless of their diagnosis of SUI, OAB symptoms, or mixed urinary incontinence (26).…”
Section: Discussionmentioning
confidence: 98%
“…Despite the very frequent complaints of sexual dysfunction, menopause related signs and symptoms and a negative impact on the quality of life in women with fibromyalgia, [15][16][17][18][19][20] and despite previous studies showing positive effects of pelvic floor kinesiotherapy for these complaints, 21,22 to date there were no reports in the literature on the use of this intervention as part of the treatment of such disorders considering this particular group of climacteric women. Thus, this is the first report in the literature pointing out that the clinical impact of pelvic floor kinesiotherapy is different in women with an associated diagnosis of fibromyalgia, which may have important implications for the clinical management of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] A recent study in Nigerian women in the climacteric phase, which aimed to investigate the effect of a twelveweek program of physical exercises and pelvic floor muscle strengthening, showed that the intervention led to a significant improvement on quality of life in general. 24 Although fibromyalgia is directly linked to emotional and psychological disorders, 25 the climacteric period, by itself, is a difficult transition phase, which involves a complex process of emotional and bodily changes, being under the influence of multiple factors such as personal and family life history, environment, culture, customs and personal peculiarities.…”
Section: Discussionmentioning
confidence: 99%